EhVps35, a retromer component, is a key factor in secretion, motility, and tissue invasion by Entamoeba histolytica - Díaz-Valdez, Joselin; Javier-Reyna, Rosario; Galindo, Ausencio; Salazar-Villatoro, Lizbeth; Montaño, Sarita; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2024)
In humans and Drosophila melanogaster, the functional convergence of the endosomal sorting complex required for transport (ESCRT) machinery that is in charge of selecting ubiquitinated proteins for sorting into multivesicular bodies, and the retromer, that is the complex responsible for protein recycling to the plasma membrane and Golgi apparatus. ESCRT and retromer complexes are codependent for protein sorting recycling, degradation, and secretion. In this article, we studied the EhVps35 C isoform (referred to as EhVps35), that is the central member of the Entamoeba histolytica retromer, and its relation with the ESCRT machinery during sorting and protein recycling events and their involvement virulence. Our findings revealed that EhVps35 interacts with at least 300 proteins that participate in multiple cellular processes. Laser confocal and transmission electronic microscopy images, as well as secretion assays, revealed that EhVps35 is secreted in vesicles together with EhVps23 and EhADH (both ESCRT machinery proteins). In addition, immunoprecipitation, immunofluorescence, and molecular docking assays revealed the relationship among EhVps35 and other ESCRT machinery proteins. Red blood cell stimulus increased EhVps35 secretion, and the knockdown of the Ehvps35 gene in trophozoites reduced their capacity to migrate and invade tissues. This also impacts the cellular localization of ubiquitin, EhVps23 (ESCRT-I), and EhVps32 (ESCRT-III) proteins, strongly suggesting their functional relationship. Our results, taken together, give evidence that EhVps35 is a key factor in E. histolytica virulence mechanisms and that it, together with the ESCRT machinery components and other regulatory proteins, is involved in vesicle trafficking, secretion, migration, and cell proliferation.